Typification of Ficus sect. Americanae (Moraceae): F. aurea and F. pertusa complexes - Pederneiras, Leandro Cardoso; Mitidieri-Rivera, Nicole; Romaniuc-Neto, Sergio; Mansano, Vidal De Freitas (Phytotaxa, 2021)
Lectotypes are designated for following 14 binomials: Ficus chaparensis, F. complicata, F. garcesii, F. halliana, F. morantensis, F. ochroleuca, F. venusta, Pharmacosycea peruviana, Urostigma baccatum, U. cestrifolium forma major, U. erythrostictum, U. populneum forma mexicanum, U. sapidum, and U. subtriplinervium forma ellipticum. Corrections of citations are made in F. palmicida, F. savannarum, U. geminum and U. subtriplinervium forma major.